Air refiner breather/disinfection unit (water seal system) is a clinically useful and cost-effective device for COVID-19 patients (Mediscope, 2022)
Coronavirus disease-2019 (COVID- 19) pandemic declared by the World Health Organization (WHO) on 11th March 2020, caused by the SARS-CoV-2 virus is at an exponentially rising state across the globe. Bangladesh is also facing the toll of this highly transmissible zoonotic disease with community transmission (at a different rate) across the country. This is a new coronavirus, still evolving, and has put the scientific authority in a puzzle. Prevention of transmission and contamination (especially via air-borne route) is the main aim here. Moreover, prevention of contamination of Intensive care unit (ICU) and operation theater (OT) equipment and environment is an optimal target. Gas and smoke evacuation during laparoscopy and pneumoperitoneum is also a big question. Cost-effectiveness is another important aspect. Different processes, techniques, devices, etc. have been tried so far. Here, a new device is going to be reported in this paper in such relation.Mediscope 2022;9(2): 81-84